Can occur hormesis in guinea grass using glyphosate? - Gallardo, Gianmarco J. T. [UNESP] (2021)
Background: Recent studies have demonstrated an increase in plant growth due to the application of low doses of glyphosate, which is part of the phenomenon known as hormesis. Objective: The present study aimed to evaluate the effects of glyphosate doses on the physiological and morphological parameters of Panicum maximum cv. Mombasa. Methods: The experiment was carried out in a greenhouse for 49 days after the application of glyphosate, in pots arranged in a completely randomized design, with four replications. The treatments consisted of ten doses of glyphosate (0; 3.78; 8.10; 16.64; 33.48; 67.7; 135; 270; 540 and 1,080 g a.e. ha-1). Evaluations of growth, gas exchange, leaf temperature and plants' intoxication were carried out. The data were subjected to ANOVA and when significant, regression analysis was performed using the models for dose-response curves. Results: The physiological parameters, as well as the growth, were positively affected by the subdoses of glyphosate, with higher values than the control. The leaf temperature increased progressively according to the increase in doses. Conclusion: Subdoses of 3.78 to 270 g a.e. ha(-1) of glyphosate promoted an increase in plant's growth and physiological parameters.